Role of public involvement in the Royal College of Physicians' Future Hospitals healthcare improvement programme: an evaluation. Issue 9 (12th September 2019) - Frith, Lucy; Hepworth, Lauren; Lowers, Victoria; Joseph, Frank; Davies, Elizabeth; Gabbay, Mark
Abstract : Objectives: The Royal College of Physician's (RCP) Future Hospital Programme (FHP) set out a blueprint for a radical new model of care that put patient experience centre stage. This paper reports on the results of an independent evaluation of the FHP and focuses on the role public patient involvement (PPI) played in these projects. The paper explores the perceptions and experiences of those involved in the FHP of how PPI was operationalised in this context, and develops an 'ex-post' programme theory of PPI in the FHP. We conclude by assessing the benefits and challenges of this work. Setting: Secondary care. The FHP consisted of eight clinician-led healthcare improvement hospital development sites with two phases. Participants: Development site clinical teams, patient representatives, the RCP's Patient and Carer Network, members of the FHP team, and fellows and members of the RCP. Design/methods: We conducted an independent evaluation of the FHP using FHP documentation and data collected specifically for the evaluation: qualitative interviews, focus groups and a web-based survey. Results: The PPI initiatives set out to develop more patient-centred care and improve the patient experience. The mechanisms designed to meet these goals were (1) a programme of PPI in the development site's projects, (2) a better understanding of patient experience and (3) evaluation of patient experience. Conclusion: This evaluation of the FHP identifies some key elements that need to be considered when attempting to more closely integrate PPI and co-production in service re-design. The structure of FHP over two phases enabled learning from phase I to be incorporated into phase II. Having the PPI representatives closely involved, developing communities of practice, and the oversight and measuring activities acted as 'disciplinary structures' that contributed to embedding PPI in the FHP and kept the patient experience at the forefront of the improvement initiatives.